2019
DOI: 10.1094/pdis-09-18-1592-re
|View full text |Cite
|
Sign up to set email alerts
|

Activity of Demethylation Inhibitor Fungicide Metconazole on Chinese Fusarium graminearum Species Complex and Its Application in Carbendazim-Resistance Management of Fusarium Head Blight in Wheat

Abstract: Fusarium graminearum species complex (FGSC), causing Fusarium head blight (FHB) of wheat, has species-specific geographical distributions in wheat-growing regions. In recent years, benzimidazole resistance of FHB pathogens has been largely widespread in China. Although the demethylation inhibitor fungicide metconazole has been used for FHB control in some countries, no information about metconazole sensitivity of Chinese FHB pathogen populations and efficacy of metconazole in FHB control in China is available.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 42 publications
2
26
0
Order By: Relevance
“…The results showed that the range of EC 50 values to metconazole for the 119 F. graminearum isolates recovered from Henan wheat fields were 0.0103 to 0.0775 μg/ml with an average EC 50 value of 0.0293 ± 0.0114 μg/ml. In previous studies, similar results were detected in the Jiangsu F. graminearum population to metconazole with EC 50 values ranging from 0.0209 to 0.0838 μg/ml and an average of 0.0481 ± 0.0134 μg/ml (Duan et al, 2019). The mean EC 50 value of the Brazilian F. graminearum population from wheat fields was 0.037 μg/ml (Spolti et al, 2012), and the EC 50 value of 80% of 101 F. graminearum isolates recovered from wheat fields in Japan was lower than 0.1 μg/ ml (Tateishi et al, 2010).…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…The results showed that the range of EC 50 values to metconazole for the 119 F. graminearum isolates recovered from Henan wheat fields were 0.0103 to 0.0775 μg/ml with an average EC 50 value of 0.0293 ± 0.0114 μg/ml. In previous studies, similar results were detected in the Jiangsu F. graminearum population to metconazole with EC 50 values ranging from 0.0209 to 0.0838 μg/ml and an average of 0.0481 ± 0.0134 μg/ml (Duan et al, 2019). The mean EC 50 value of the Brazilian F. graminearum population from wheat fields was 0.037 μg/ml (Spolti et al, 2012), and the EC 50 value of 80% of 101 F. graminearum isolates recovered from wheat fields in Japan was lower than 0.1 μg/ ml (Tateishi et al, 2010).…”
Section: Discussionsupporting
confidence: 81%
“…As resistance in the FGSC population is seen to increase to fungicides belonging to benzimidazoles and cyanoacrylates, it is recommended to include the use of metconazole in control programmes against FHB. The DMI fungicide metconazole has high activity against F. graminearum (Duan et al, ). In the current study conducted during 2016 and 2017, the susceptibility of the Henan F. graminearum population that had no previous exposure to metconazole was determined by inhibiting mycelial growth.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, phenamacril has a high resistance risk in FGSC [10]. Previous studies have reported a strong correlation between FHB control efficacy and DON contamination [32,37,38,39]. Therefore, it is necessary to find novel fungicides for controlling FHB and DON contamination caused by FGSC.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have proved that tebuconazole alone at varied concentrations or in combination with other fungicides was effective in inhibiting FHB and DON, and the drug showed optimal performance at the early anthesis stage or later anthesis stage [147,148,149,150]. The sensitivities of FHB pathogens to metconazole and the efficacy of this fungicide in FHB and DON control in China were reported in a recent study; metconazole exhibited better efficacy than phenamacril and carbendazim [151]. Propiconazole also had a certain role in toxin management [148], but it was reported that this fungicide may have the opposite effect on toxin control at low doses.…”
Section: Fusarium Toxin Managementmentioning
confidence: 99%